Mission and context - Havea, Jione (Theology in the age of empire, 2020)
The visions that guide and drive mission are oftentimes blinded by power, position, protection, and plenitude. This collection of writings from minoritized settings in Africa, Asia, the Americas, and Oceania, examines those matters with queering attention to the shadows that empires cast over the contexts of mission and to the collusion and complicity of Christians and churches with empires past and present. The authors interweave the principles and practices of mission with the opportunities in decolonial theology and hermeneutics, minoritized and migrant Christologies, repatriation, indigenous insights and wisdom, stories of resistance and endurance in zones of contact and violence, and life-centered spiritual encountering